Magnetic resonance imaging of pulmonary and paranasal sinus abnormalities in children with primary ciliary dyskinesia compared to children with cystic fibrosis - Wucherpfennig, Lena; Wünnemann, Felix; Eichinger, Monika; Schmitt, Niclas; Seitz, Angelika; Baumann, Ingo; Roehmel, Jobst F.; Stahl, Mirjam; Hämmerling, Susanne Hedwig; Chung, Jaehi; Schenk, Jens-Peter; Alrajab, Abdulsattar; et al. (Annals of the American Thoracic Society, 2024)
Rationale: Primary ciliary dyskinesia (PCD) and cystic fibrosis (CF) are characterized by inherited impaired mucociliary clearance leading to chronic progressive lung disease as well as chronic rhinosinusitis (CRS). The diseases share morphological and functional commonalities on magnetic resonance imaging (MRI) of the lungs and paranasal sinuses, but comparative MRI studies are lacking. - - Objectives: To determine whether PCD shows different associations of pulmonary and paranasal sinus abnormalities on MRI and lung function test results in children (infants to adolescents) compared with children with CF. - - Methods: Eighteen children with PCD (median age, 9.5 [IQR, 3.4-12.7] yr; range, 0-18 yr) and 36 age-matched CF transmembrane conductance regulator modulator-naive children with CF (median age, 9.4 [3.4-13.2] yr; range, 0-18 yr) underwent same-session chest and paranasal sinus MRI as well as spirometry (to determine forced expiratory volume in 1 s percent predicted) and multiple-breath washout (to determine lung clearance index z-score). Pulmonary and paranasal sinus abnormalities were assessed using previously validated chest MRI and CRS-MRI scoring systems. - - Results: Mean chest MRI global score was similar in children with PCD and CF (15.0 [13.5-20.8] vs. 15.0 [9.0-15.0]; P = 0.601). Consolidations were more prevalent and severe in children with PCD (56% vs. 25% and 1.0 [0.0-2.8] vs. 0.0 [0.0-0.3], respectively; P < 0.05). The chest MRI global score correlated moderately with forced expiratory volume in 1 second percent predicted in children with PCD and children with CF (r = −0.523 and −0.687; P < 0.01) and with lung clearance index in children with CF (r = 0.650; P < 0.001) but not in PCD (r = 0.353; P = 0.196). CRS-MRI sum score and mucopyocele subscore were lower in children with PCD than in children with CF (27.5 [26.3-32.0] vs. 37.0 [37.8-40.0] and 2.0 [0.0-2.0] vs. 7.5 [4.8-9.0], respectively; P < 0.01). CRS-MRI sum score did not correlate with chest MRI score in PCD (r = 0.075-0.157; P = 0.557-0.788) but correlated moderately with MRI morphology score in CF (r = 0.437; P < 0.01). - - Conclusions: MRI detects differences in lung and paranasal sinus abnormalities between children with PCD and those with CF. Lung disease does not correlate with CRS in PCD but correlates in CF.